Facile 1D graphene fiber synthesis from an agricultural by-product: A silicon-mediated graphenization route - Fujisawa, K.; Lei, Y.; Tomas Andres, Carla de; Suarez-Martinez, Irene; Zhou, C.; Lin, Y.; Subramanian, S.; Elías, A.; Fujishige, M.; Takeuchi, K.; Robinson, J.; Marks, N.; et al. (Pergamon, 2019)
© 2018 Elsevier Ltd A one-dimensional (1D) graphene fiber with a novel structure has been prepared by a heat treatment of rice husk, a natural by-product that contains high amounts of silica. A step-by-step heat treatment of rice husk revealed that (i) carbonization yields porous carbon and silica, (ii) 1D ß-SiC nanowires are formed by the carbothermic reduction of silica, (iii) finally 1D graphene fibers are created by silicon sublimation from 1D ß-SiC nanowires. Raman spectroscopy and electron microscopy studies revealed that the graphene fiber is composed of a turbostratic multilayer structure. The SiC-derived material exhibits a large crystalline size and turbostratic stacking making each layer as quasi-free-standing graphene, which is confirmed by the 3.9 times higher Raman G'-band intensity over the G-band intensity. Molecular dynamics simulations revealed a high diffusion rate of Si atoms and a volume reduction of the SiC structure at the sublimation temperature. Since the silicon sublimation occurred from multiple points of the SiC nanowire, this led to radially-collapsed fibers and faceted structures with thick-graphitic-layer that are inter-connected (deflated-balloons and inter-connected balloon-like fibers). This facile synthesis route opens up a new avenue to the cost-effective and etching-free production of self-standing graphene for its bulk usage.